2009
DOI: 10.1007/s12205-009-0423-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of bridge deformation using GPS technique

Abstract: Tianjin Yonghe Bridge is one of the important infrastructures in China where it serves as the crucial links in the transport network. Monitoring and maintenance of this bridge are essential tasks in prolonging its life. In this paper, GPS system was used for deformation data collection. Two analytical methods namely; Kalman Filter (KF) and Parametric Least Square (PLS) were used for the adjustment of these data. The analysis of test results indicate that: (1) the traffic loads are the main factor affects bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…The KF and Least Square (LS) are two types of wavelet analysis used in a wide area of GPS applications. It was found that the calculated coordinates from LS and KF analysis methods are much closer [7].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The KF and Least Square (LS) are two types of wavelet analysis used in a wide area of GPS applications. It was found that the calculated coordinates from LS and KF analysis methods are much closer [7].…”
Section: Introductionmentioning
confidence: 86%
“…The entire width of the bridge deck is 13.6m, including lane road of 9m and the pavement on both sides of the bridge. The bridge is a five-span continuous prestressed concrete cable-stayed bridge with the main span of 260m, double pylons and double columns [7].…”
Section: Introductionmentioning
confidence: 99%
“…. e use of GPS receivers related to SHM has been implemented in several investigations [1,[3][4][5][6][7][8][9], resulting that GPS is an advanced tool for this kind of purposes. e main advantage of GPS is its capability of measuring directly displacements without the requirement of double integration of accelerations; generally necessary in other devices.…”
Section: Geodetic-grade Gps Receiversmentioning
confidence: 99%
“…Since two decades ago, both geodetic-grade GPS (Global Positioning System) receivers and commercial accelerometers have been used in several studies related to Structural Health Monitoring (SHM) [1][2][3][4][5][6][7][8][9]. e results of these investigations demonstrated that they are efficient and accurate devices for SHM of roads, dams, buildings, bridges, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of Global Navigation Satellite Systems (GNSS) for deformation monitoring is a common practice, e.g. for crustal movements, landslides, structure and infrastructure deformations (Kaloop and Li, 2009, Fastellini et al, 2011, Barzaghi et al, 2018. The GNSS monitoring system is typically implemented installing a network of receivers that guarantee a millimeter accuracy, usually computing solutions on daily periods.…”
Section: Gnss Monitoringmentioning
confidence: 99%